Dengue-Associated Posterior Reversible Encephalopathy Syndrome - Manya, Sharath M.; Mahalingam, Soundarya; Raeesa, Fathima; Srivatsav, Sathya (Journal of Pediatric Neurology, 2020)
Dengue fever has been associated with a myriad of complications, due to widespread inflammation in the various afflicted organs. Central nervous system (CNS) complications include encephalitis, encephalopathy, intracranial bleed, and spinal and cranial nerve involvement with varied outcomes. We report a case of an adolescent girl who presented with dengue fever and significant hypotension requiring intravenous fluids and vasopressors, and developed seizures on the third day of admission. Magnetic resonance imaging (MRI) of brain showed features suggestive of posterior reversible encephalopathy syndrome. She was managed conservatively with antiepileptics. She showed complete clinical recovery over the next 3 days and remained normal with seizure freedom at a recent follow-up after tapering antiepileptics.
Keywords: posterior reversible encephalopathy syndrome; dengue fever; adolescent girl